Fixing prisoners from psychosocial point of view (The Journal of Psychology and Sociology, 2017)
This article discusses how to fix prisoners from psychosocial point of view. According to penal execution code of Republic of Kazakhstan there was told about fixed assets how to fix convicts. Also this article discusses psychosocial worker’s benefits in fixing prisoners. Penal execution system is directed to mitigation of atonement of punishment and strengthening of attention to influence and creation of the moral environment at punishment atonement. Therefore at improvement of penal executional system an important part is psychosocial service. The main aims of experts of psychosocial service are: raising the effectiveness of correcting exposure, beneficial use of human factors during the work with experts, to optimize relationship between convicts and staff. Ensuring social and psychological works with convicts, suspects and prosecutors consists from: researching prisoners in investigative detention, prepared offers when convicts with mental disorders, when they are suicidal behaviors, determining the dispositions of injury to organs of the body, correcting by psychological methods and conducting psychoprophylactic actions. Also, if they are offered to be free before the period and are offered to change colonies, allowed to go round without guard, the the prisoners will be conducted psychological diagnosis.For people who are convicted at colonies will be conducted psychological preparation. Psychologists are ready to help for people who are convicted in various conflict situations. The main aim of observing prisoners personality– is to select useful methods of psychological affect, and the main task of penitentiary psychologists– is to change criminal directions of prisoners. To stop swamped circle of crime, to avoid preventable right violation or to downsize the level of affecting criminal society concerning specific person. As a main aim of psychological service is accepted modern psychological science and increasing effectiveness of accomplishing punishment in terms of using practical achievements. The main functions of psychological services are also mentioned in the article.
Keywords: Penal Execution Code of the Republic of Kazakhstan; Penal Code of the Republic of Kazakhstan; correction of convict; influence of correction; articles of correction; establishment of management; socially-psychological service.